When Figurative Frames Decrease Political Persuasion: The Case of Right-Wing Anti-Immigration Rhetoric. Issue 3 (16th March 2021) - Boeynaems, Amber; Burgers, Christian; Konijn, Elly A.
ABSTRACT: The rhetoric used by right-wing anti-immigration politicians is considered important to their political success. Such rhetoric commonly contains figurative frames with metaphor and/or hyperbole. In two experiments ( n experiment1 = 411, n experiment2 = 407), we tested when and how such figurative frames add to the intense and emotive character of anti-immigration statements and their subsequent persuasiveness. Results showed that different voters respond differently to figuratively framed anti-immigration rhetoric: overall, voters perceived figuratively framed populist statements as more intense and emotive than nonfigurative statements, which caused boomerang effects by decreasing political persuasion. By contrast, right-wing populist voters were not persuaded by rhetorical variations in anti-immigration statements. Our findings underscore how anti-immigration rhetoric can broaden the gap between voters and put in motion further polarization in our society.